2014
DOI: 10.1371/journal.pone.0111192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gunshot Entrance Morphologies Caused by .40-Caliber Smith & Wesson, .380-Caliber, and 9-mm Luger Bullets: A Finite Element Analysis Study

Abstract: Firearms can cause fatal wounds, which can be identified by traces on or around the body. However, there are cases where neither the bullet nor gun is found at the crime scene. Ballistic research involving finite element models can reproduce computational biomechanical conditions, without compromising bioethics, as they involve no direct tests on animals or humans. This study aims to compare the morphologies of gunshot entrance holes caused by.40-caliber Smith & Wesson (S&W), .380-caliber, and 9×19-mm Luger bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
(39 reference statements)
3
17
0
Order By: Relevance
“…Studies have shown that the algorithm of Sugeno-type gives high performance, but involves quite complex learning procedure. The obtained results correspond to the conclusions of some other researchers who studied the possibility of applying the neural network approach to the solution of various problems (Matoso et al, 2014;Xue et al, 2015;Jang, 1993). The accuracy of obtained numerical estimates is provided by using standard means of MATLAB.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies have shown that the algorithm of Sugeno-type gives high performance, but involves quite complex learning procedure. The obtained results correspond to the conclusions of some other researchers who studied the possibility of applying the neural network approach to the solution of various problems (Matoso et al, 2014;Xue et al, 2015;Jang, 1993). The accuracy of obtained numerical estimates is provided by using standard means of MATLAB.…”
Section: Discussionsupporting
confidence: 80%
“…Over the last few years, there have been proposed a lot of methods for face identification (Geman et al, 2015), on the basis of which, automatic systems for human faces recognition are developed: Smith & Wesson (Matoso et al, 2014) (ASID system -Automated Suspect Identification System); ImageWare (Xue et al, 2015) (system FaceID); Imagis (Grother et al, 2015), Epic Solutions (Kotwal et al, 2012), Miros (Trueface system) (Sharma et al, 2013); Vissage Technology (Vissage Gallery system) (Monroe, 2009); Visionics (FaceIt system) (Parmar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we used the geometrical shape of a rhombus. Matoso et al [9] in their study have proven that different morphologies in the entrance holes are produces by three different calibers, using the same skull at the same shot distance of 10 cm. A 9 mm caliber wound was irregular and triangular, while a 10 mm caliber wound was round.…”
Section: Discussionmentioning
confidence: 97%
“…This difference may be due to the loss of gyroscopic stability that occurs when the bullets strike and pass through an intermediate barrier, 18,19,13 the structure of vehicles in this case, as well as the occurrence of their flattening/deformation resulting from the same interaction. 13 Regarding the removal of bullets from the victims' bodies, this only occurred in cases 3 and 6. The lack of an exit wound is an expected result when the bullet crosses an intermediate target before hitting the victim.…”
Section: E Rodrigues Et Al / Journal Of Forensic and Legal Medicinementioning
confidence: 99%
“…When bullets strike motor vehicle structures, their behaviour will be influenced by a number of factors including their velocity, energy and construction (mass, shape and material properties), as well as the angle of incidence 10 and material they pass through (metal or glass). The terminal wound ballistics performance in the body of the occupants of the vehicles will essentially depend on the bullet's characteristics, 11,12,8 the effects arising from the interaction with the vehicle's structure, 8 the occurrence of fragmentation and/ or deformation of the bullets, 11 the amount of kinetic energy and momentum 12 with which the bullets strike human tissue, 11,13 the nature of the affected tissues 14,15 and the anatomical area and anatomical structures that are impacted. 15 The most common bullet associated with police shootings is the 9 mm Luger full metal jacket (FMJ) round nose.…”
Section: Introductionmentioning
confidence: 99%